The Impact of Venture Capital Monitoring - BERNSTEIN, SHAI; GIROUD, XAVIER; TOWNSEND, RICHARD R. (Journal of Finance, 2016)
ABSTRACT We show that venture capitalists' (VCs) on‐site involvement with their portfolio companies leads to an increase in both innovation and the likelihood of a successful exit. We rule out selection effects by exploiting an exogenous source of variation in VC involvement: the introduction of new airline routes that reduce VCs' travel times to their existing portfolio companies. We confirm the importance of this channel by conducting a large‐scale survey of VCs, of whom almost 90% indicate that direct flights increase their interaction with their portfolio companies and management, and help them better understand companies' activities.